PENGEMBANGAN BUDIDAYA MAGGOT (HERMETIA ILLUCENS) SEBAGAI PAKAN IKAN ALTERNATIF YANG MURAH DAN RAMAH LINGKUNGAN - Suwarsito, Suwarsito; Mulia, Dini Siswani; Mustafidah, Hindayati (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
The waste problem in Dukuhwaluh Village was still a lot of household waste thrown away in any places. This household waste causes unpleasant odors, environmental pollution, various disease outbreaks, aesthetic disturbances, and flooding during the rainy season. Another problem encountered in Dukuhwaluh Village is the provision of feed for catfish farmers, the price of which is increasingly expensive. This causes the development of the catfish farming business to be very slow and even threatened with collapse. This community service activity aims to increase the knowledge and skills of fish farmers in Dukuh Waluh Village in cultivating maggots using media from household organic waste. This community service activity also aims to develop magot as an alternative fish food that is cheap, has high nutritional value and is environmentally friendly. The implementation of this community service uses research-based community empowerment methods. Meanwhile, the approach method used in implementing community service is active and collaborative participation. The results of community service activities can increase the knowledge and skills of the Dukuhwaluh Village fish farmer in maggot cultivation. The fish farmer group has also been able to practice magot cultivation using household organic waste properly and correctly, as well as applying the results of maggot cultivation to feed catfish.